2000
DOI: 10.1007/s005350050343
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal mucosal acid sensitivity can coexist with normal pH recording in healthy adult volunteers

Abstract: We aimed to determine whether healthy volunteers with normal pH monitoring study results experienced heartburn or discomfort during an esophageal acid perfusion test. We performed an esophageal acid perfusion test, followed by ambulatory esophageal pH monitoring, in 15 healthy and asymptomatic volunteers (aged 19 to 34 years). The results of the acid perfusion test were correlated with those of the pH monitoring. Three subjects (20%) reported chest discomfort during acid perfusion. The pH data in all subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
1
8
1
Order By: Relevance
“…In a study by Ho et al,20.0% of healthy subjects were found to have a positive APT [6]. This positivity rate in healthy individuals is remarkably close to the positivity rates found in the SI-negative patients studied by King and colleagues.…”
Section: To the Editorsupporting
confidence: 83%
“…In a study by Ho et al,20.0% of healthy subjects were found to have a positive APT [6]. This positivity rate in healthy individuals is remarkably close to the positivity rates found in the SI-negative patients studied by King and colleagues.…”
Section: To the Editorsupporting
confidence: 83%
“…This could be confirmed by repeating the test after healing of esophageal mucosa, but we did not find a study designed in this manner in the literature. We postulate that the Bernstein test results for our GERD patients cannot be explained solely by erosive lesions because studies with healthy volunteers with normal pH monitoring results have revealed 15-20% Bernstein test positivity [15,16]. In our study patients with LPR had a 25% Bernstein test positivity, which is approximately the result in normal individuals.…”
Section: Discussionmentioning
confidence: 52%
“…Although highly specific and sensitive for the diagnosis of GERD, the 24-h pH monitoring is limited in its applications because of the dynamic nature of the disease. Studies have shown that its results are normal in 25% of patients with erosive esophagitis and in approximately 33% of patients with NERD [8]. Patients who report reflux symptoms may thus not test positive during pH monitoring.…”
Section: Discussionmentioning
confidence: 97%